Data collection and reporting on human trafficking in Canada - Baglay, Sasha; Atak, Idil (Frontiers in Human Dynamics, 2025)
The article discusses the challenges of data collection in the context of anti-human trafficking efforts in Canada. It aims to identify existing statistical data from government sources and stimulate discussions around data accuracy and availability. The analysis indicates that the available data predominantly focuses on crime-related statistics, highlighting the need for improved data practices. The article’s conceptual framework emphasizes open government as crucial for democratic governance, advocating for data availability and Access to Information (ATI) regimes that promote transparency and empower public engagement. It stresses that reliable data is vital for evidence-based policymaking, particularly in Canada, where responses to human trafficking have often been largely rhetorical and enforcement-centric. Structured in four parts, the article first outlines international standards for data collection on human trafficking. It then situates the research within open government principles, discusses the specific complexities of data reporting in Canada, and shares insights from the authors’ data collection experiences through ATI requests. The conclusion raises critical questions to guide future efforts in enhancing data collection and reporting processes related to human trafficking.